Powers of the Mind: Mental and Manual Labor in the Contemporary Political Crisis - Bray, Michael (transcript, 2019)
The Marxist conception of the division between mental and manual labor is a critical yet unrecognized aspect of contemporary political struggles.Departing from this novel argument, Michael Bray traces the conceptual and socio-political history of this labor division and emphasizes how the forms of control and organization articulated by that division in practices of production, democracy, racialization, and financialization are becoming increasingly important. Critiquing the left for its tendency to side implicitly with the powers of mental labor, Michael Bray shows that comprehending and challenging those powers is a pivotal task for anti-capitalist politics today.